A Proposed Model to Generate New Revenue Streams for Telecommunications Customer Service Providers (CSP) by Leveraging the Existing Infrastructure and Market Reach - Shamkant Atale, Abhijit (Digital Repository of Theses, 2025)
Telecommunications Customer Services Providers, also known as customer service providers or CSPs have experienced a significant drop in their profitability in recent years. This phenomenon is global, in developed and developing markets alike. With new developments in the technology around 5G, IoT, Cloud, Blockchain and AI, many new avenues for revenue growth are opening up for the Telecom Service Providers (CSPs). While many Telecom Service Providers (CSPs) have tried various initiatives with new technologies, it has given only moderate success so far. There is no clear business model which would unlock sustainable and profitable growth for the Telecom Service Providers (CSPs). Through this research, I have tried to co-relate inside-out and outside-in perspectives through targeted interviews with senior professionals associated with the Telecom industry as well as consumers of telecom services in retail and enterprise segments, in to derive a framework model for the Telecom Service Providers (CSPs) to return to profitable growth, backed up with a comprehensive set of recommendations for the Telecom Service Providers (CSPs) to adopt in their business strategy for the future.